Archetypal Values in French: some theoretical considerations - Yasena Chantova (Scientific Results, 2025)
This article explores the theoretical intersections between Jungian archetypes and the semantic domain of the language sciences, with a focus on French. It examines how archetypal entities, defined by their representations and socio-cultural values, interact with linguistic structures. By contrasting Jung’s archetypes with prototype semantics (Kleiber) and interpretive semantics (Rastier), the study highlights their incompatibilities and shared insights. To address the epistemological gap between psychoanalysis and linguistics, the article turns to Saussure’s notion of valeur, particularly in the Écrits, to propose the concept of archetypal values as a neo-Saussurean framework for semantic analysis